Pengembangan Media Komik Digital Flipbook Berbantuan Canva pada Materi Proses Fotosintesis Kelas IV SDN 1 Moyoketen - Scarviexsa Prasasti Susanto; Ria Fajrin Rizqy Ana (Jurnal Simki Postgraduate, 2024)
This research is motivated by the lack of use of technology in the learning media used, teachers still use textbooks, worksheet books and several classic learning media. This research aims to develop digital flipbook comic media assisted by Canva on photosynthesis process material, determine the validity and applicability of digital flipbook comic media assisted by Canva on photosynthesis process material. This research uses the ADDIE development model including Analysis, Design, Development, Implementation, Evaluation. Data collection techniques were carried out using questionnaires and documentation. The test subjects in this research were 2 media experts, 1 material expert and 21 class IV students at SDN 1 Moyoketen. The results of the research show that the level of validity of Canva-assisted flipbook digital comic media on photosynthesis process material from media expert 1 got a score of 78% and media expert 2 got a score of 88%, while material expert validation got a score of 86%, the applicability assessment was taken from the student questionnaire with a score 99%. From this research, it can be concluded that the development of digital flipbook comic media with the help of Canva on photosynthesis material for class IV SDN 1 Moyoketen is valid and can be applied to learning so that learning is more enjoyable.